Understanding the relevance of philosophy for the modern Muslim - Abdul Razak, Mohd Abbas; Artalim Zaim, Muntaha (IIUM-Today, 2025)
Through this article, we would like to explore some of the important reasons for learning philosophy as a subject. Before delving into a deeper discussion, let us first consider some peripheral information related to philosophy. More often than not, most students of philosophy are introduced to the subject by making Greece their point of departure. For people in the West, Greece is an important country because it is considered the birthplace of Western civilization, democracy, education, and liberal thought. However, philosophy as a field of study was not confined to ancient Greece alone. Concurrent with the flourishing of philosophy in Greece, people in Persia, India, and China were also engaged in philosophical thought.